Kampania wyborcza na fotelu prezydenckim – skuteczne metody zarządzania informacją w mieście - Jadachowska, Anna (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2012)
The paper discusses the role new media play in the information policy of a politician running for office based on the example of the campaign run by the candidate for the office of president of Radomsko, Anna Milczanowska. As the Internet is becoming increasingly influential and the interest in social platforms increases, the assumptions of PR activities have changed. The paper emphasizes that at present the senders of a message do not require traditional media to reach the recipient. It demonstrates that the proverbial ‘single click’ of a mouse is sufficient to notify thousands about the sender’s activities. This thoroughly changes the position of PR officers, as one-way communication has been replaced by a two-way dialogue once and for all. Local authorities have obtained a new tool which on the one hand facilitates genuine contact, but on the other, subjects them to a greater degree of social assessment.